2021
DOI: 10.3390/en14051505
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Renewable Energy in Myanmar: Energy Source Preference

Abstract: The increased use of renewable energy is imperative as a countermeasure to climate change. As with conventional electricity generation technologies, public acceptance of renewables is an important issue, and willingness to pay (WTP) is a widely used indicator to assess such public attitudes. Unfortunately, the literature to date mostly covers developed countries, with few WTP surveys in developing countries. Tackling climate change is an urgent issue for these developing countries; therefore, understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Later, there was little research on WTP photovoltaic power generation in Asian underdeveloped economies [ 29 ], only the research on WTP, a renewable energy source, in China [ 30 ], India [ 22 ], Indonesia [ 25 ], Kazakhstan [ 31 ], Laos [ 32 ], Pakistan [ 33 ], However, due to the frequent occurrence of extreme weather, more and more CVM methods are used to study the sustainable development strategy of solar energy [ 34 , 35 ], photovoltaic power generation is a major form of utilizing solar energy [ 36 ], and its potential evaluation, technology optimization and cost calculation are gradually brought into the research field of vision [ 37 ]. Meanwhile, the influencing factors of photovoltaic power generation WTP vary from country to country, including social status [ 38 ], gender [ 14 ], perceived willingness to pay [ 39 ], the frequency of payment [ 40 ], political party and race [ 41 ], awareness of environmental protection [ 10 ], renewable type [ 42 45 ].…”
Section: Literature Review For Solar Photovoltaic Power Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, there was little research on WTP photovoltaic power generation in Asian underdeveloped economies [ 29 ], only the research on WTP, a renewable energy source, in China [ 30 ], India [ 22 ], Indonesia [ 25 ], Kazakhstan [ 31 ], Laos [ 32 ], Pakistan [ 33 ], However, due to the frequent occurrence of extreme weather, more and more CVM methods are used to study the sustainable development strategy of solar energy [ 34 , 35 ], photovoltaic power generation is a major form of utilizing solar energy [ 36 ], and its potential evaluation, technology optimization and cost calculation are gradually brought into the research field of vision [ 37 ]. Meanwhile, the influencing factors of photovoltaic power generation WTP vary from country to country, including social status [ 38 ], gender [ 14 ], perceived willingness to pay [ 39 ], the frequency of payment [ 40 ], political party and race [ 41 ], awareness of environmental protection [ 10 ], renewable type [ 42 45 ].…”
Section: Literature Review For Solar Photovoltaic Power Generationmentioning
confidence: 99%
“…Jin Tianyu [ 7 ] thinks that take the promulgation of Compulsory Education Law as an instrumental variable, this paper solves the causal relationship between higher education and willingness to pay for environmental protection. Numata et al [ 29 ] pointed out that the potential mechanism of school education on individual behavior may be that it improves the way individuals deal with new information, has critical thinking skills, or provides the right tools to make more informed behavior decisions.…”
Section: Literature Review For Solar Photovoltaic Power Generationmentioning
confidence: 99%
“…In the case of developing countries, although there is an increasing number of studies on the WTP for renewable energy (see for example Numata et al 2021;Bakessen & Schuler 2020;Entele 2020;Han et al 2020;Jin et al 2019;Xiea & Zhao 2018;Azlina et al 2018;Osiolo 2017;Alam & Bhattacharyya 2017;Ghosh et al 2017), the WTP for renewable energy of Malaysian consumers has not been widely explored yet. In fact, the highlights of past studies for the contingent valuation method in Malaysia have been widely used in other fields such as tourism (Samdin et al 2008;Yacob et al 2009), conservation (Hassan-Basri et al 2020, Adamu et al 2015Thalany), transportation (Hassan-Basri et al 2019, water services (Mahirah et al 2019, Mahirah et al 2018.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have been conducted in different countries to analyze consumer behavior, and willingness to pay for sustainable alternatives to natural resources Consumers were willing to pay for renewable energy sources in Japan (Nomura and Akai, 2004), England (Longo et al, 2007;Scarpa and Willis, 2010), Greece (Damigos et al, 2009;Ntanos et al, 2018;Karasmanaki and Tsantopoulos, 2019), Crete (Zografakis et al, 2010), Cambodia (Yoeu and Pabuayon, 2011), U.S. (Murakami et al, 2014), South Korea (Lee et al, 2017), China (Ali et al, 2019), Poland (Pyzalska, 2019), Turkey (Muhammad et al, 2020), Nigeria, (Ayodele et al, 2021), Myanmar (Numata et al, 2021), Netherlands (Pleeging et al, 2021), Aguascalientes, Mexico (Martinez and Nunez, 2021). In Pakistan, (Ifat et al, 2020;Iqbal et al, 2020) concluded that people are willing to pay for renewable or green energy sources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, household decisions regarding solar, wind, biomass, and other renewable energy sources have been studied. Numata et al (2021) and Borchers et al (2007) have compared various renewable energy sources. Both studies indicate that people prefer solar energy to other renewable energy sources.…”
Section: Literature Reviewmentioning
confidence: 99%